Mastering Compound Word for Teachers and Learners of English - Jimmi Jimmi; Juniato Sidauruk (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Abstract -- This study focuses on compound word and its need to be mastered by teachers and English learners. There are new words coming up almost every day. Most of them are by combining of two different words, blending and many other morphological phenomena. It is commonly known as word-formation. The discussion covers on word-formation specifically on the types of compound word and its meaning.   A new word is formed from the same or different word classes. This word formation must be mastered by the English teachers and also the learners of English. The Semantic theory is used just to study the meaning of the word not the sentence. This research uses descriptive qualitative method. The data were  taken from The Time of the Oath Album By Helloween. The results show that there are three types compound words found. Compound Noun is the most dominant followed by Adjective and Verb. The Endocentric Compound is the most productive compound in meaning. Keywords: Compound, Endocentric, Lyrics, Morphology, Word-formation